SHARIA BANKING FINANCING MODEL IN ENHANCING THE HALAL CERTIFICATION OF MICRO, SMALL, MEDIUM ENTERPRISE INDUSTRY - Nasrulloh, Nasrulloh (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2021)
A large number of Micro, Small, Medium Enterprise (MSMEs) that did not have a halal certificate yet due to lack of funds is one of the main problems in the failure of the implementation of the JPH Law mission. Halal Product Certification Agency (BPJPH) demands all products sold in Indonesia ought to have a halal certificate in 2019. This study aims to provide a model solution from the financial institution side. Islamic banking as a sharia financial institution has a strategic part to help MSMEs, offer a variety of contracts, and make MSMEs able to carry out halal certification processes. By using descriptive-analytic method, the results of this study offer the financing model with murÄbahah and mudhÄrabah contract. The financing model with a murÄbahah contract is applied as in the common purchasing contract. While the financing model with a mudharabah should be adjusted to the principle of profit-loss sharing with some period adjustment. The implication of this research shows that Islamic Banking can be an intermediary between the community and BPJPH. The submission process of halal certificates through the Islamic banks cooperation is considered easier, more efficient, and transparent.Â